Effects of Clinician-Guided Emergent Literacy Intervention Using Interactive Tablet Technology for Preschool Children With Cochlear Implants. (August 2017) - Brouwer, Kyle; Downing, Hannah; Westhoff, Sara; Wait, Ryann; Entwisle, Lavin K.; Messersmith, Jessica J.; Hanson, Elizabeth K.
The purpose of this study was to investigate if intervention based on a mobile application would improve the print knowledge and vocabulary of preschool children with and without hearing loss. This was a multiple baseline study that included four preschool children. Two of the children had hearing loss and utilized cochlear implants, while the other two had normal hearing. Clinicians utilized a mobile application to facilitate print knowledge (i.e., sound-symbol relationships) and to acquire new vocabulary. By the end of the study, all four children demonstrated improved familiarity with the targeted letter sounds and improved knowledge of the vocabulary words that were utilized during the study. The results of this study indicate that the mobile application, in combination with clinician scaffolding, was an effective tool for facilitating early literacy skills in preschool children. Prior print knowledge and vocabulary development appeared to be stronger indicators of response to treatment than hearing status.